Relative value of carotenoid pigments of new-crop (1954) yellow corn and old-crop (1948-49 government stored) yellow corn and of dehydrated alfalfa for supplying the Vitamin A requirements of weanling pigs. - Parrish, D.B.; Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Question has been raised concerning the vitamin A potency of stored yellow corn. Samples of 1954 corn and 1948-49 stored corn were analyzed for provitamin A content by a separation and chemical determination of the carotene and crude cryptoxanthin contents. The 1948-49 sample was found to have a vitamin A activity of about 800 units per pound, slightly less than one-third of that of 1964 corn. In this work 1 mg. of carotene was given a vitamin A value of 1.6 unit-s and cryptoxanthin one-half that value, which are the vitamin A activities previously determined by bioassay with rats. Although much vitamin A activity apparently had been lost during storage of yellow corn, there was still the problem of the availability of the remaining vitamin A for animals. This was studied, using weanling pigs as the experimental animal.
Keywords: Swine; Carotenoid; Yellow corn; Dehydrated alfalfa; Vitamin A; Weanling pigs